SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166487-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solutions for Gas Displacements with Bifurcating Phase Behavior

Abstract: Minimum miscibility pressure (MMP) is one of the most important parameters in the design of a successful gas flooding process. The most reliable methods to calculate the MMP are based on slim-tube experiments, 1-D slim-tube simulations, mixing cell calculations, and the analytical methods known as the method of characteristics (MOC). The calculation of MMP using MOC is the fastest method because it relies solely on finding the key tie lines in the displacement path. The MOC method for MMP estimation in its cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…This behavior is anomalous because normally the tie line between F and S should be longer than the other sides of the tie triangle. However, this behavior could occur if phase behavior bifurcates (a critical point separates into two critical points) as was demonstrated by Khorsandi et al (2013). The simulation results are inconclusive above 1600 psia as they were difficult to obtain at these pressures and many simulations failed.…”
Section: Example Calculationsmentioning
confidence: 97%
See 1 more Smart Citation
“…This behavior is anomalous because normally the tie line between F and S should be longer than the other sides of the tie triangle. However, this behavior could occur if phase behavior bifurcates (a critical point separates into two critical points) as was demonstrated by Khorsandi et al (2013). The simulation results are inconclusive above 1600 psia as they were difficult to obtain at these pressures and many simulations failed.…”
Section: Example Calculationsmentioning
confidence: 97%
“…Further, the analytical solutions for twophase displacements with complex phase behavior that bifurcates into a L 1 -L 2 and L 1 -V region (similar to three-phase systems) have not yet been extended to displacements with more than three components. Khorsandi et al (2013) showed that for such complex ternary displacements the MMP does not exist for some oil and gas compositions. In those cases, L 1 -L 2 behavior exists for all higher pressures even though the displacement efficiency is high (greater than 95%) so that effectively a pressure is reached where high displacement efficiency occurs.…”
Section: Introductionmentioning
confidence: 99%
“…However, heavy oil is typically depleted of the C 2 -C 5 hydrocarbons and the miscible mixture between any heavy oil and CO 2 may only be achieved at pressures in excess of safe reservoir operational conditions (i.e., above fracture pressure). Furthermore, minimum miscibility pressure (MMP) may not exist for some heavy oils (Khorsandi et al, 2014). The reservoir pressure should ideally be close to and preferably higher than MMP to have a high efficiency CO 2 flood, and ultimate storage efficiency.…”
Section: Physics Of Co 2 Floodsmentioning
confidence: 99%
“…Li et al (2014b) extended mixing cell methods to three-phase displacements. The multiple mixing cell method of Ahmadi and Johns (2011) is accurate even for complicated phase behavior (Mogensen et al 2009, PennPVT toolkit manual 2013, Rezaveisi et al 2015, Khorsandi et al 2014. Nevertheless, it would still be useful to have other computational methods, such as those based on MOC, as another check of the MMP.…”
mentioning
confidence: 99%